Comparison of catchment and network delineation approaches in complex suburban environments: application to the Chaudanne catchment, France. Issue 25 (20th September 2012) - Jankowfsky, Sonja; Branger, Flora; Braud, Isabelle; Gironás, Jorge; Rodriguez, Fabrice
Abstract Suburban areas are subject to strong anthropogenic modifications, which can influence hydrological processes. Sewer systems, ditches, sewer overflow devices and retention basins are introduced and large surface areas are sealed off. The knowledge of accurate flow paths and watershed boundaries in these suburban areas is important for storm water management, hydrological modelling and hydrological data analysis. This study proposes a new method for the determination of the drainage network based on time efficient field investigations and integration of sewer system maps into the drainage network for small catchments of up to 10 km2. A new method is also proposed for the delineation of subcatchments and thus the catchment area. The subcatchments are delineated using a combination of an object‐oriented approach in the urban zone and geographical information system–based terrain analysis with flow direction forcing in the rural zone. The method is applied to the Chaudanne catchment, which belongs to the Yzeron river network and is located in the suburban area of Lyon, France. The resulting subcatchment map gives information about subcatchment response and contribution. The method is compared with six other automatic catchment delineation methods based on stream burning, flow direction forcing and calculation of subcatchments for inlet points. None of the automatic methods could correctly represent the catchment area and flow paths observed in the field. The watershed area calculated with these methods differs by as much as 25% from the area computed with the new method. Copyright © 2012 John Wiley & Sons, Ltd.